Hungarian Seniors - A New Promising Target? - Deli-Gray, Zsuzsa; Árva, László (Marketing & Menedzsment, 2019)
The market of the senior people has recently received increased attention in many parts of the world where the elder people had relatively high level of disposable income, looked more for good quality and healthy products, searched more for leisure time activities and for new hobbies than before reaching their “senior” status. In Central and Eastern Europe the officially drawn picture of the seniors looks quite different. According to the statistics most of the senior people have problems with earning the money to cover their costs, try to restructure their spending, and become introverted and separated from the other parts of the society. Global companies targeting seniors in many different regions should, in light of this picture, build this difference into their operative strategies in order to be efficient in all markets.